2022
DOI: 10.52711/0974-360x.2022.00634
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory effects of Zingiber officinale (Ginger): A Systematic Review

Abstract: Recently, the available synthetic drugs to treat immune related diseases have been reported to produce many side effects to the consumer. For instance, corticosteroids are used to reduce inflammation during infection but able to cause adverse effects such as bruising, muscle weakness, pathologic fractures, weight gain and sleep disturbances. As an alternative for a safer alternative for preventive and treatment agents with low risk of side effect, Zingiber officinale which is known as ginger or ‘halia’ in Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Accordingly, it was noted that the preference rates of linden, sage and marsh mallow decreased significantly, while the preference rates of ginger, turmeric, thyme, galangal, olive leaf, black cumin, agarwood, carob, pine cone and hibiscus increased. While plants were generally used to reduce the symptoms of the common cold before the pandemic, it can be said that plants that strengthen the immune system started to be preferred in order to prevent COVID-19 during the pandemic period [13][14][15][16][17][18]. Therefore, plants such as linden, sage and marsh mallow were replaced by other plants such as ginger, turmeric and thyme.…”
Section: Evaluation Of the Results Of Information Formmentioning
confidence: 99%
“…Accordingly, it was noted that the preference rates of linden, sage and marsh mallow decreased significantly, while the preference rates of ginger, turmeric, thyme, galangal, olive leaf, black cumin, agarwood, carob, pine cone and hibiscus increased. While plants were generally used to reduce the symptoms of the common cold before the pandemic, it can be said that plants that strengthen the immune system started to be preferred in order to prevent COVID-19 during the pandemic period [13][14][15][16][17][18]. Therefore, plants such as linden, sage and marsh mallow were replaced by other plants such as ginger, turmeric and thyme.…”
Section: Evaluation Of the Results Of Information Formmentioning
confidence: 99%
“… Qian et al (2023) demonstrated that a ginger polysaccharide, UGP1; reduced tumor proliferation in tumor-bearing mice; raised the p53 expression and the ratio of Bax/Bcl-2; enhanced proinflammatory cytokine secretion, TNF-α, IL-2, IL-6; and decreased the secretion of pro-tumor cytokines TGF-β and bFGF in serum. The ethanol and aqueous extracts of Z. officinale decreased the inflammatory cell infiltration around the airways and decreased the elevated levels of IL-4 and IL-5 in the lungs and BALF of BALB/c mice compared to methylprednisolone as a control group (Khan et al, 2015; Harun and Mohamad, 2022 ). In another in vivo study, 6-gingerol in phosphate-buffered saline reduced IL-17 infiltration from the peripheral blood into the central nervous system, as well as neuroinflammation and demyelination ( Han et al, 2019 ; Harun and Mohamad, 2022 ).…”
Section: Immunomodulating Effects Of Zingiber Speciesmentioning
confidence: 99%
“…The ethanol and aqueous extracts of Z. officinale decreased the inflammatory cell infiltration around the airways and decreased the elevated levels of IL-4 and IL-5 in the lungs and BALF of BALB/c mice compared to methylprednisolone as a control group (Khan et al, 2015; Harun and Mohamad, 2022 ). In another in vivo study, 6-gingerol in phosphate-buffered saline reduced IL-17 infiltration from the peripheral blood into the central nervous system, as well as neuroinflammation and demyelination ( Han et al, 2019 ; Harun and Mohamad, 2022 ). In Albino rats with necrotizing enterocolitis, a whole ginger aqueous extract (1,000 mg/kg/day) lowered IL-1, TNF-α, and IL-6 levels ( Cakir et al, 2018 ; Harun and Mohamad, 2022 ).…”
Section: Immunomodulating Effects Of Zingiber Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jahe adalah zat antioksidan yang kuat dan dapat mengurangi atau mencegah pembentukan radikal bebas (Wakchaure & Ganguly, 2018). Hasil penelitian berupa systematic review dari 11 penelitian RCT (Randomized Clinical Trial) terkait efektivitas jahe sebagai imunomodulator menunjukkan efek positif baik dari penelitian in vitro maupun in vivo (Hikmah Harun & Firdaus Mohamad, 2022). Kunyit (curcuma longa) dan temulawak (curcuma xanthorrhiza) diketahui mengandung senyawa aktif kurkuminoid (Nurcholis et al, 2015).…”
Section: Gambar 1 Kafe DI Wisata Rainbow Gardenunclassified